2023
DOI: 10.1186/s12864-023-09453-8
|View full text |Cite
|
Sign up to set email alerts
|

Chimeras in Merlot grapevine revealed by phased assembly

Abstract: Chimerism is the phenomenon when several genotypes coexist in a single individual. Used to understand plant ontogenesis they also have been valorised through new cultivar breeding. Viticulture has been taking economic advantage out of chimeras when the variant induced an important modification of wine type such as berry skin colour. Crucial agronomic characters may also be impacted by chimeras that aren’t identified yet. Periclinal chimera where the variant has entirely colonised a cell layer is the most stabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Our dataset revealed that the number of somatic mutations within one grapevine plant, when comparing distinct shoots (Merlot WT shoots and Merlot WB shoots), is similar to those found between grapevine clones (Table 1 ), with between 351,018 and 356,754 shoot-specific SNVs being identified in Merlot (Additional file 16: Table S6 ). The counts of shoot-specific SNVs in Merlot is higher than the number of intra-organisms SNVs that have been identified in grapevine (3.2-3.7k) [ 62 ] and other plant systems (4.9k SNVs in Zostera marina and 44-152k SNVs in Populus trichocarpa ) [ 63 , 64 ]. This is likely in large part due to the differences in methods used between our study and previous studies due to the differences in the aims of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our dataset revealed that the number of somatic mutations within one grapevine plant, when comparing distinct shoots (Merlot WT shoots and Merlot WB shoots), is similar to those found between grapevine clones (Table 1 ), with between 351,018 and 356,754 shoot-specific SNVs being identified in Merlot (Additional file 16: Table S6 ). The counts of shoot-specific SNVs in Merlot is higher than the number of intra-organisms SNVs that have been identified in grapevine (3.2-3.7k) [ 62 ] and other plant systems (4.9k SNVs in Zostera marina and 44-152k SNVs in Populus trichocarpa ) [ 63 , 64 ]. This is likely in large part due to the differences in methods used between our study and previous studies due to the differences in the aims of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely in large part due to the differences in methods used between our study and previous studies due to the differences in the aims of the studies. Given that the main goal of this study was to identify putative causal variants of WB, we did not apply stringent filtering that these previous studies have applied [ 62 64 ].…”
Section: Discussionmentioning
confidence: 99%